Intuitive concepts in elementary topology - Arnold, B. H. (Bradford Henry) 1916- (Dover books on mathematics, 2011)
"Classroom-tested and much-cited, this concise text is designed for undergraduates. It offers a valuable and instructive introduction to the basic concepts of topology, taking an intuitive rather than an axiomatic viewpoint. Well illustrated with figures and diagrams, it can serve as either a primary text or a valuable supplement. 1962 edition"--Provided by publisher.